Quantitative Susceptibility Mapping and Resting State Network Analyses in Parkinsonian Phenotypes—A Systematic Review of the Literature - Pelzer, Esther A.; Florin, Esther; Schnitzler, Alfons (Frontiers in Neural Circuits, 2019)
An imbalance of iron metabolism with consecutive aggregation of α-synuclein and an axonal degeneration of neurons has been postulated as main pathological feature in the development of Parkinson's disease. Quantitative susceptibility mapping (QSM) is a new imaging technique, which enables to measure structural changes caused by defective iron deposition in parkinsonian brains. Due to its novelty, its potential for disease specific characterisation of motor and non-motor symptoms (characterizing the individual parkinsonian phenotype) as new imaging technique remains elusive. Functional network changes associated with these symptoms are however frequently described for both, magnetoencephalography (MEG) and resting state functional magnetic imaging (rs-fMRI). Here, we performed a systematic review of the current literature about QSM imaging, MEG and rs-fMRI in order to collect existing data about structural and functional changes caused by motor and non-motor symptoms in Parkinson's disease. Whereas all three techniques provide an affection in the motor domain, the understanding of network changes caused by non-motor symptoms is much more lacking for MEG and rs-fMRI, and do not yet really exist for QSM imaging. In order to better understand the influence of pathological iron distribution onto the functional outcome, whole brain QSM analyses should be integrated in functional analyses (especially for the non-motor domain), to enable a proper pathophysiological interpretation of MEG and rs-fMRI network changes in Parkinson's disease. Herewith, a better understanding of the relationship between neuropathological changes, functional network changes and clinical phenotype might become possible.